2011
DOI: 10.1590/s1806-37132011000200012
|View full text |Cite
|
Sign up to set email alerts
|

Características de pacientes com DPOC internados em UTI de um hospital de referência para doenças respiratórias no Brasil

Abstract: Objective: To report data regarding COPD patients admitted to the ICU of a referral hospital for respiratory diseases, including outcomes and treatment evaluation. Methods: Study of a series of patients with respiratory failure and COPD admitted to the ICU of Nereu Ramos Hospital, located in the city of Florianópolis, Brazil, between October of 2006 and October of 2007. Data related to demographics, causes of hospitalization, pharmacological treatment, ventilatory support, length of hospital stay, in-hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 26 publications
2
10
0
8
Order By: Relevance
“…One study showed that 50% of COPD patients admitted to the ICU for respiratory failure used systemic corticosteroids, meaning that at least 50% of the patients had received inappropriate non-pharmacological treatment. ( 10 ) This reinforces the hypothesis that the use of clinical protocols is low, given that none of the major clinical protocols in Brazil include the use of systemic corticosteroids as a treatment option. ( 1 , 8 ) …”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…One study showed that 50% of COPD patients admitted to the ICU for respiratory failure used systemic corticosteroids, meaning that at least 50% of the patients had received inappropriate non-pharmacological treatment. ( 10 ) This reinforces the hypothesis that the use of clinical protocols is low, given that none of the major clinical protocols in Brazil include the use of systemic corticosteroids as a treatment option. ( 1 , 8 ) …”
Section: Discussionsupporting
confidence: 68%
“…( 2 ) A study evaluating COPD patients with respiratory failure admitted to the ICU also showed low vaccination rates, only 66.66% having received influenza vaccination and only 45.83% having received pneumococcal vaccination. ( 10 ) Only 6.5% of the patients in the present study received pulmonary rehabilitation, which is recommended in the 2011 GOLD guidelines for patients in categories B, C, and D. Other studies have shown low rates of pulmonary rehabilitation. In one study, only 14% of the patients hospitalized for COPD exacerbation had received prior pulmonary rehabilitation.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…(22) Regarding the frequent use of drugs for obstructive airway diseases, it can be explained by the fact that respiratory diseases, such as chronic obstructive pulmonary disease (COPD) and pneumonia, are frequent causes of hospitalization in ICU. (23) ICU inpatients usually undergo painful procedures, so the use of analgesics to provide comfort to inpatients is a priority in intensive care. (24) The number of items per patient without repetition of the drug were not included in this study.…”
Section: Discussionmentioning
confidence: 99%